The anatomical scaffold underlying the functional centrality of known cortical hubs. Issue 10 (6th July 2017) - de Pasquale, Francesco; Della Penna, Stefania; Sabatini, Umberto; Caravasso Falletta, Chiara; Peran, Patrice
Abstract: Cortical hubs play a fundamental role in the functional architecture of brain connectivity at rest. However, the anatomical scaffold underlying their centrality is still under debate. Certainly, the brain function and anatomy are significantly entwined through synaptogenesis and pruning mechanisms that continuously reshape structural and functional connections. Thus, if hubs are expected to exhibit a large number of direct anatomical connections with the rest of the brain, such a dense wiring is extremely inefficient in energetic terms. In this work, we investigate these aspects on fMRI and DTI data from a set of know resting‐state networks, starting from the hypothesis that to promote integration, functional, and anatomical connections link different areas at different scales or hierarchies. Thus, we focused on the role of functional hubs in this hierarchical organization of functional and anatomical architectures. We found that these regions, from a structural point of view, are first linked to each other and successively to the rest of the brain. Thus, functionally central nodes seem to show few strong anatomical connections. These findings suggest an efficient strategy of the investigated cortical hubs in exploiting few direct anatomical connections to link functional hubs among each other that eventually reach the rest of the considered nodes through local indirect tracts. Hum Brain Mapp 38:5141–5160, 2017 . © 2017 Wiley Periodicals, Inc.